Molecular pathology and clinical treatment of independent HPV primary serous carcinoma of the uterine cervix (USCC): A case report - Lina Niu; Fangying Ruan; Qisheng Yang; Chaoran Xia; Tao Xu; Fei Dong; Lizhen Zhang; Sheng Guo; Weiqin Lv; Junxia Wang; Yun Shang (Clinical Case Reports, 2023)
Abstract On October 23, 2020, a 69‐year‐old Chinese female patient was admitted to Yuncheng Hospital due to a history of postmenopausal bleeding and lower abdominal pain for 5 months. The HPV test and pathology results indicated the presence of independent HPV in primary serous carcinoma of the uterine cervix. The genetic testing identified variants of uncertain significance (PAX8 p.Tyr 410 Ter and TP53 p.Asn 247 Ile), microsatellite instability stable (MSI‐S), tumor mutational burden (TMB) 7.33Muts/Mb, and an elevated tumor neoantigen burden. Before undergoing radical hysterectomy treatment, the patient exhibited a positive response to three cycles of intravenous docetaxel (100 mg/3 h) and carboplatin (450 mg/1 h). Following the surgery, she received an additional three cycles of docetaxel (100 mg/3 h) and carboplatin (500 mg/1 h), accompanied by 25 cycles of radiation therapy (DT 46Gy/2Gy/23f). Concurrently, cisplatin (450 mg/1 h) was administered. As of now, the patient has achieved 20 months of disease‐free survival.